PEMANFAATAN MOBILE BANKING SERTA INTERNET BANKING PADA MASA PANDEMI COVID-19 PADA PT BANK SYARIAH MANDIRI KANTOR CABANG TANGERANG BSD - Alida Wahyuni; Eriana Dinda Putyri (Institut Teknologi dan Bisnis Swadharma, 2021)
Covid-19 pandemic has an impact on all sectors, including the banking sector. Especially in banking customer transaction services due to the Large-Scale Social Restrictions (PSBB) implemented by the Indonesian government. Mobile Banking and Internet Banking are facilities that can facilitate banking transactions. Customers do not need to visit branch offices or ATMs to make transactions such as fund transfers, balance checks, account mutation checks, or payments. Only by using smartphones or computer devices, customers can easily and comfortably make transactions during the pandemic. Mobile banking is one of the bank services that are in great demand by customers because this service enables bank customers to perform banking transactions via smartphones. Mandiri Syariah Mobile (MSM), an application provided by the Bank to provide banking services to customers through the Bank's electronic distribution channels to access accounts held by customers at the Bank through a communication network using a cellular phone or tablet computer